Клад раннесредневекового кузнеца на Харьковщине - Колода, В.В. (Хазарский альманах, 2020)
The plentiful material complex, a blacksmith’s buried treasure, that was discovered near Varvarovka in Kharkov oblast (Ukraine), is analyzed in the article. A set of crafting tools included a portable framed anvil, two hammers, two tongs, snips, a punch, and three fi les. Some forging stock and remains of other things of a black metal were found here as well. Besides, the complex consisted of two fi les for processing of soft natural materials (wood, bone or horn), sheep shears, and the general purpose implements: a knife, an ax, and a stitching awl. Also, there were artifacts made of nonferrous metal, which played the role of raw materials for bronze-casting production.